2000
DOI: 10.1002/1521-4141(200010)30:10<2900::aid-immu2900>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of MHC class I-stimulated alloresponses by TNF/TNF receptor (TNFR)1 interactions and of MHC class II-stimulated alloresponses by TNF/TNFR2 interactions

Abstract: In vivo TNF inhibition has been observed to ameliorate the disease process attributed to T cell‐dependent immune responses such as those generated during graft‐vs.‐host disease. The present studies were designed to evaluate whether TNF/TNF receptor (TNFR)1 and TNF/TNFR2 interactions were involved in the generation of allospecific T cell responses. Splenic lymphocyte populations were obtained from TNFR1‐ or TNFR2‐deficient B6 mice and from control B6 mice. These responder cells were cultured with irradiated MHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…We have previously observed that TNF/TNFR2 interactions on responder CD4 ϩ T cells are critical for optimal alloproliferation and Th1 cytokine responses by T cells in response to alloantigenic stimuli in vitro or in vivo during intestinal GVHD (30). As TNF has been reported to stimulate IL-12 production by macrophages (6), these earlier results suggested that TNF may amplify Th1 cytokine responses by an indirect effect on IL-12 production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously observed that TNF/TNFR2 interactions on responder CD4 ϩ T cells are critical for optimal alloproliferation and Th1 cytokine responses by T cells in response to alloantigenic stimuli in vitro or in vivo during intestinal GVHD (30). As TNF has been reported to stimulate IL-12 production by macrophages (6), these earlier results suggested that TNF may amplify Th1 cytokine responses by an indirect effect on IL-12 production.…”
Section: Discussionmentioning
confidence: 99%
“…Triplicate wells of control B6 or B6.IL-12R Ϫ/Ϫ responder spleen cells (3 ϫ 10 5 ) were cultured with irradiated MHC class II disparate bm12 (3 ϫ 10 5 ) or irradiated syngeneic stimulator cells (3 ϫ 10 5 ) in the presence or absence of a chimeric TNF inhibitor protein (0.5 g/ml) for 3 days before assay of [ 3 H]thymidine incorporation, as previously described (30).…”
Section: Mixed Lymphocyte Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 TNFRII promotes T-cell proliferation and MHC class II-stimulated alloresponses. 36 TNF-TNFRII interactions are critical for the development of aGVHD in animal models and recombinant human soluble TNFRII fusion protein is currently used to treat steroid refractory GVHD. 37,38 Our study indicates that transplants involving recipients and/or donors with TNFRII 196 T/T genotype had a higher risk of aGVHD, though the influence was not TNFA, TNFB and TNFRII gene polymorphisms and allo-HSCT H Xiao et al significant in an HLA-matched cohort and using multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%